2012
DOI: 10.1080/14689367.2011.594787
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous generalized synchronization of chaos

Abstract: International audienceWe study synchronization functions in basic examples of discontinuous forced systems with contractive response and chaotic driving. The forcing is given by baker-type maps and the response is assumed to depend monotonically on the drive. The resulting synchronization functions have dense sets of discontinuities and their graphs appear to be extremely choppy. We show that these functions have bounded variation when the contraction is strong, and conversely, that their total variation is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…where T : [0, 1] → [0, 1] (and, again, the mapping f 2 will play no role here). For a systematic way of defining f such that f −1 is as here, see [10]. Assuming in addition that the filter satisfies…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where T : [0, 1] → [0, 1] (and, again, the mapping f 2 will play no role here). For a systematic way of defining f such that f −1 is as here, see [10]. Assuming in addition that the filter satisfies…”
Section: Resultsmentioning
confidence: 99%
“…The sync function has been shown to be of bounded variation under the condition e htop(f −1 ) γ < 1 where h top (f −1 ) is the topological entropy of f −1 . On the other hand, the total variation of φ becomes infinite when γ is sufficiently large [10]. A sync function of bounded variation makes it easier to show that the factor statistics inherits absolute continuity of the forcing statistics [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when h is of bounded variation, a decomposition into the difference h c − h d of increasing functions, where in addition h c is continuous and h d is a step function, is provided. (This is the only result of [5] that is being used here, see lemma 3. )…”
Section: (W N+1 Z N+1 ) = (F (W N ) G(w N Z N ))mentioning
confidence: 90%
“…In [5], the first author analyses properties of the function h. In particular, it is shown that the total variation is finite iff λ < 1/2. Moreover, when h is of bounded variation, a decomposition into the difference h c − h d of increasing functions, where in addition h c is continuous and h d is a step function, is provided.…”
Section: (W N+1 Z N+1 ) = (F (W N ) G(w N Z N ))mentioning
confidence: 99%
See 1 more Smart Citation